Negative health effects of dental X-rays: A systematic review - Laila Wiklander; Andreas Cederlund; Nils Kadesjö; Peggy Näsman; Sofia Tranaeus; Aron Naimi-Akbar (PLoS ONE, 2025)
Background This study evaluates whether exposure to dental X-ray examinations in childhood and adolescence results in negative health effects. Material and methods This systematic review includes both primary studies and systematic reviews available in Medline, Embase, and Web of Science databases. Six reviewers read the full text of the selected studies. Results The literature search resulted in 10,949 publications. After title and abstract screening, 55 publications were selected for full text reading, resulting in a total of 18 reports, 7 systematic reviews, and 11 primary studies for quality assessment. Conclusion None of the selected studies passed the quality assessment due to high or very high risk of bias. There is a gap of knowledge regarding negative effects of dental X-rays and a need for more accurate and updated studies.